The Application of Red Guava and Orange Juice Innovation to Boost Hemoglobin as an Effort to Prevent Anemia - sri ernawati; Anita; Syastriani Isna Putri Syarif; Dian Astuti; Tiwi Laboto; Rasni; Rita Artika (Poltekkes Kemenkes Kendari, 2026)
Anemia in pregnant women remains a serious health problem that can increase the risk of delivery complications and stunting. This Community Service activity aims to improve the literacy and skills of pregnant women in the working area of Sulaa Health Center, Baubau City through the application of innovative combination juice of red guava (Psidium guajava) and orange (Citrus) as a natural nutritional alternative for increasing hemoglobin. The implementation methods included nutritional counseling, juice-making demonstration, and regular consumption assistance conducted in January-February 2026 involving 15 pregnant women as participants. The results showed an 80% increase in respondents' literacy about the dangers of anemia (from 6 to 12 people who understood), and an 80% increase in understanding of the benefits and how to make combination juice (from 5 to 12 people who understood). The willingness evaluation showed that 73% of pregnant women (11 out of 15) committed to consuming the juice independently as a complementary effort alongside Iron Supplement Tablets (TTD) consumption. The combination of red guava, rich in iron and vitamin C, and orange with high vitamin C content, proved effective as an affordable non-pharmacological solution. This program is expected to reduce the anemia rate and strengthen community empowerment in utilizing nutrition based on local wisdom. Keywords: Anemia, Guava, Hemoglobin, Orange, Pregnant Women